2022
DOI: 10.3389/fpubh.2022.857561
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction of Telemedicine in Pediatric and Young Adult Type 1 Diabetes Patients During Covid-19 Pandemic

Abstract: The aim of this study was to evaluate the satisfaction of the use of telemedicine and telenursing in children and young adults with Type 1 Diabetes and their families followed in the Regional Pediatric Diabetes Center of Giannina Gaslini Institute (Liguria, Italy). An anonymous survey form was administered to 290 patients (138 filled out by caregivers and 152 by patients). The questionnaire consisted of two parts: the first one included a series of questions related to the patient's personal and medical data; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 27 publications
3
27
0
5
Order By: Relevance
“…Use in preference to usual care was explored in 4 studies. In 1 study [ 63 ], families reported use of telehealth beyond the coronavirus pandemic was not wanted, and in 3 studies [ 50 , 64 , 68 ], parents emphasized it was wanted to supplement but not substitute in-person clinics.…”
Section: Resultsmentioning
confidence: 99%
“…Use in preference to usual care was explored in 4 studies. In 1 study [ 63 ], families reported use of telehealth beyond the coronavirus pandemic was not wanted, and in 3 studies [ 50 , 64 , 68 ], parents emphasized it was wanted to supplement but not substitute in-person clinics.…”
Section: Resultsmentioning
confidence: 99%
“…Con todo, la teleenfermería es una solución para responder a estos desafíos y necesidades de eficiencia a distancia y limitaciones de costos (27) . Asimismo, tiene muchos beneficios en la situación actual y es una medida práctica y confiable en la planificación e implementación efectiva de intervenciones que tienen un impacto positivo en la salud pública (28,29) , por tanto, la teleenfermería debe ser incorporada en la formación universitaria e impulsada a través de cursos y seminarios (30) .…”
Section: Discussionunclassified
“…In fact, the process of the visit (downloading and sharing data) and the objectives of the visit (empowerment of the patient and family to achieve good glycemic control) are the same as those of the traditional visit. A survey was also carried out among patients and parents, concerning the satisfaction with the televisits performed [ 48 ]. From this survey, 90% of the respondents stated that they were very satisfied with the telemedicine service, that they had no problems communicating with the doctors and that they received adequate attention for their condition.…”
Section: Telemedicine and Chronicitymentioning
confidence: 99%